2016
DOI: 10.1016/j.ijrobp.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Geographic Access to Cancer Care and Receipt of Radiation Therapy for Rectal Cancer

Abstract: Purpose Trimodality therapy (chemoradiation and surgery) is standard of care for Stage II/III rectal cancer but nearly one third of patients do not receive radiation therapy (RT). We examined the relationship between density of radiation oncologist and travel distance to receipt of RT. Materials/Methods A retrospective study based on the National Cancer Data Base identified 26,845 patients aged 18–80 with Stage II/III rectal cancer diagnosed between 2007–2010. Radiation oncologists were identified through Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 37 publications
1
69
0
5
Order By: Relevance
“…We also found that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy. 22 The distance to radiation facilities has been shown to affect the selection of treatments, that include radiotherapy (eg, breast conservation therapy and multimodality therapy), [31][32][33][34][35] and our analysis demonstrated that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy to access the limited number of proton therapy centers in the United States. Our multivariate analysis suggests that socioeconomic factors, including insurance and neighborhood income and education, are significantly associated with differences in the receipt of proton therapy versus photon therapy.…”
Section: Discussionmentioning
confidence: 73%
“…We also found that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy. 22 The distance to radiation facilities has been shown to affect the selection of treatments, that include radiotherapy (eg, breast conservation therapy and multimodality therapy), [31][32][33][34][35] and our analysis demonstrated that patients treated with proton therapy traveled significantly longer distances than those treated with photon therapy to access the limited number of proton therapy centers in the United States. Our multivariate analysis suggests that socioeconomic factors, including insurance and neighborhood income and education, are significantly associated with differences in the receipt of proton therapy versus photon therapy.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, geographic access should be considered as a significant variable associated with the receipt of treatment for LARC patients, whereas the density level of radiation oncologists cannot. Moreover, patients with nonprivate insurance who lived in low-density oncologist areas were less likely to receive the standard treatment [5,6]. socioeconomic status, age, and comorbidities.…”
Section: The Us National Cancer Database (Ncdb)mentioning
confidence: 99%
“…5 For example, increased travel distance was associated with an increasing likelihood of high-risk prostate 6 and colon cancer 7 at diagnosis. 9 Conversely, a recent report by Wasif et al, which focused exclusively on patients who underwent surgery, demonstrated that longer travel distance is associated with better long-term cancer outcomes in colon, esophageal, liver, and pancreatic malignancies. 9 Conversely, a recent report by Wasif et al, which focused exclusively on patients who underwent surgery, demonstrated that longer travel distance is associated with better long-term cancer outcomes in colon, esophageal, liver, and pancreatic malignancies.…”
Section: Introductionmentioning
confidence: 99%